2014
DOI: 10.1161/circep.114.001578
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Canine Coronary Sinus Musculature From the Atria by Radiofrequency Catheter Ablation Prevents Induction of Atrial Fibrillation

Abstract: Background-The junction between the coronary sinus (CS) musculature and both atria contributes to initiation of atrial tachyarrhythmias. The current study investigated the effects of CS isolation from the atria by radiofrequency catheter ablation on the induction and maintenance of atrial fibrillation (AF). Methods and Results-Using an optical mapping system, we mapped action potentials at 256 surface sites in 17 isolated and arterially perfused canine atrial tissues containing the entire musculature of the CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Oral et al demonstrated that in a small population with AF ablation, electrical disconnection of the CS from the LA lowered the inducibility of AF after PVI. Further study on a canine AF model also confirmed that isolating the CS from the atria eliminated AF induction . Our present study shows that an increased gradient between CSd and CSp, as in the CSd/CSp ratio, might be an independent predictor for AF termination and long‐term outcome.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Oral et al demonstrated that in a small population with AF ablation, electrical disconnection of the CS from the LA lowered the inducibility of AF after PVI. Further study on a canine AF model also confirmed that isolating the CS from the atria eliminated AF induction . Our present study shows that an increased gradient between CSd and CSp, as in the CSd/CSp ratio, might be an independent predictor for AF termination and long‐term outcome.…”
Section: Discussionsupporting
confidence: 78%
“…Further catheter ablation at CS-atrial junctions by isolating the CS from the atria eliminated the sustained AF. 21 In the current context we hypothesized whether the characteristics of CS activities would help us to identify a subset of patients in whom the electrical activities of CS might play an important role in maintenance of AF and predict the outcome of AF ablation.…”
mentioning
confidence: 99%
“…1 Canine studies have pointed to the participation of CS musculature to left atrial (LA) connections in unstable macro-reentrant atrial tachycardia (AT) and atrial flutter (AFL) with degeneration to atrial fibrillation (AF). 25 Additionally, the CS is a source of focal triggered activity in 15% of patients with AF recurrence despite pulmonary vein isolation (PVI). 6 Ablation of endocardial and epicardial aspects of the CS has been shown to prolong the fibrillatory cycle length and terminate AF in selected patients.…”
mentioning
confidence: 99%
“…Of note, while the patient was in SR, constant pacing at the inferior aspect of the ridge reproduced the same windshield wipers pattern seen during LAT within the CS ( Figure 3A The variability of the conduction through the CS-LA connections, related to their intrinsic conductive properties (conduction-delay), [2][3][4] explains the variable relationship between the endocardial and the epicardial activation.…”
Section: Case Presentationmentioning
confidence: 62%
“…1 Subsequently, elegant studies have described the electrophysiological properties of these connections as well as their potential supporting role for re-entrant tachycardias and AF. [2][3][4] Despite all these robust publications, during several years the clinical implications of these connections have been relatively neglected by the electrophysiological community. However, besides their importance in the understanding of LATs as highlighted by our observation, a recent publication has pointed out the interest of these CS-LA connections (in particular the Marshall's bundle) as potential targets for the treatment of persistent AF in humans.…”
Section: F I G U R E 1 a Activation Map Of The Latmentioning
confidence: 99%